Intentional Minds: A Philosophical Analysis of Intention Tested through fMRI Experiments Involving People with Schizophrenia, People with Autism, and Healthy Individuals - Bara, Bruno G.; Ciaramidaro, Angela; Walter, Henrik; Adenzato, Mauro (Frontiers in Human Neuroscience, 2011)
In this paper we show how we empirically tested one of the most relevant topics in philosophy of mind through a series of fMRI experiments: the classification of different types of intention. To this aim, firstly we trace a theoretical distinction among private, prospective, and communicative intentions. Second, we propose a set of predictions concerning the recognition of these three types of intention in healthy individuals, and we report the experimental results corroborating our theoretical model of intention. Third, we derive from our model predictions relevant for the domain of psychopathological functioning. In particular, we treat the cases of both hyper-intentionality (as in paranoid schizophrenia) and hypo-intentionality (as in autistic spectrum disorders). Our conclusion is that the theoretical model of intention we propose contributes to enlarge our knowledge on the neurobiological bases of intention processing, in both healthy people and in people with impairments to the neurocognitive system that underlies intention recognition.